15ab+9a=0

Simple and best practice solution for 15ab+9a=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15ab+9a=0 equation:


Simplifying
15ab + 9a = 0

Reorder the terms:
9a + 15ab = 0

Solving
9a + 15ab = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), '3a'.
3a(3 + 5b) = 0

Ignore the factor 3.

Subproblem 1

Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0

Subproblem 2

Set the factor '(3 + 5b)' equal to zero and attempt to solve: Simplifying 3 + 5b = 0 Solving 3 + 5b = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5b = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5b = 0 + -3 5b = 0 + -3 Combine like terms: 0 + -3 = -3 5b = -3 Add '-5b' to each side of the equation. 5b + -5b = -3 + -5b Combine like terms: 5b + -5b = 0 0 = -3 + -5b Simplifying 0 = -3 + -5b The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

a = {0}

See similar equations:

| X(2x+1)=6 | | 2.058/588 | | 8sin^2x-5sinx-2=0 | | 8-6(2x-9)=60 | | 250/10 | | 45-(-86)=z | | 3x-2=10x+5 | | 6c-12+3c=12 | | x-(x*0.05)=23.74 | | -900=10x | | 20/.5 | | -9(-4+5n)-(-16n+18)= | | 35x-17=10x+5 | | z=4(x+8) | | 35x-7=10x+5 | | 45-(-86)= | | 0.2-0.02(x+2)=0.05(1-x) | | 7s+2s-19s= | | x-3=10x+5 | | X^(-1/2)=0 | | 5-6.7= | | 10x+5=13x+9 | | 1.2W+4.7=-17.5 | | -2(3x-7)+2=22 | | 4f+6-7f-2= | | 13x+9=10x+5 | | -17-y=11 | | 6+7h=4h | | 0.04x^2-3x+44=0 | | 7(2m-7)-4=0 | | -5y+3y+3=y-13 | | x=9-8x |

Equations solver categories